The Influence Of Religious Understanding Towards Public Interest In Sharia Financial Institution Products - Moylina, Nona; Kambali, Muhammad; mardiaynto, eko (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2024)
This study aims to answer the problem of whether there is an influence of religious understanding on public interest in Islamic Financial Institutions. This type of research is Quantitative research. Primary data were collected with a closed questionnaire with a liket scale. The number of respondents used was 399 respondents who were spread proportionally with the Cluster Sampling Technique. The data is then analyzed using statistical methods starting with conducting validity tests, reality tests, linearity tests, normality tests then determining regression models, T tests and Determination Coefficient Tests. The results of this study show that there is a significant influence of religious understanding variables on public interest. This is indicated by the calculated T value of 27.709 and the Sig. value of 0.000. So that the value of t is calculated > t table which is 27.709 > 1.649 and the value of Sig. which is 0.000 < 0.05. The amount of influence of this religious understanding variable was obtained by 64.5% while the remaining 35.5% was influenced by other variables. The results of this study help financial industry stakeholders to continue to improve socialization and community literacy in Islamic finance. The results of this research are also a strong basis for strengthening cooperation between stakeholders in the Islamic finance industry and religious leaders.